Evaluation of Cases of Abdominal Wall Endometriosis at Universidade Estadual de Campinas in a period of 10 Years - Daniela Angerame Yela; Lucas Trigo; Cristina Laguna Benetti-Pinto (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2017)
Abstract Purpose To determine the clinical and epidemiological characteristics of abdominal wall endometriosis (AWE), as well as the rate and recurrence factors for the disease. Methods A retrospective study of 52 women with AWE was performed at Universidade Estadual de Campinas from 2004 to 2014. Of the 231 surgeries performed for the diagnosis of endometriosis, 52 women were found to have abdominal wall endometriosis (AWE). The frequencies, means and standard deviations of the clinical characteristics of these women were calculated, as well as the recurrence rate of AWE. To determine the risk factors for disease recurrence, Fisher's exact test was used. Results The mean age of the patients was 30.71 ± 5.91 years. The main clinical manifestations were pain (98%) and sensation of a mass (36.5%).We observed that 94% of these women had undergone at least 1 cesarean section, and 73% had used medication for the postoperative control of endometriosis. The lesion was most commonly located in the cesarean section scar (65%). The recurrence rate of the disease was of 26.9%. All 14 women who had relapsed had surgical margins compromised in the previous surgery. There was no correlation between recurrent AWE and a previous cesarean section (p = 0.18), previous laparotomy (p = 0.11), previous laparoscopy (p = 0.12) and postoperative hormone therapy (p = 0.51). Conclusion Women with previous cesarean sections with local pain or lumps should be investigated for AWE. The recurrence of AWE is high, especially when the first surgery is not appropriate and leaves compromised surgical margins.